2020
DOI: 10.1257/app.20180306
|View full text |Cite
|
Sign up to set email alerts
|

A Precinct Too Far: Turnout and Voting Costs

Abstract: I study the effects of voting costs—specifically, distance to polling location—using geographic discontinuities. Opposite sides of boundaries between voting precincts are observationally identical, except for their assigned polling locations. This discontinuous assignment produces sharp changes in voters’ travel distance to cast their ballots. In nine municipalities in Massachusetts and Minnesota, a 1 standard deviation (0.245 mile) increase in distance reduces ballots cast by 2 to 5 percent across four electi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 41 publications
0
43
1
1
Order By: Relevance
“…For example, Brady and McNulty (2011) examined changes in polling place location due to the consolidation of precincts in Los Angeles County during California’s 2003 gubernatorial recall election, and found that turnout at the polling place was reduced by about 3 percentage points among individuals for whom the polling place had changed. Similarly, Cantoni (2020) examined geographic discontinuities in travel distance to polling places based on precinct boundaries, and found that increasing travel distance by about 0.25 miles decreased voter turnout by 2 to 5 percentage points – in our case the relocated precincts moved by an average of about 0.25 miles (although the distance to the polling place did not necessarily increase for all voters in the treated precincts).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…For example, Brady and McNulty (2011) examined changes in polling place location due to the consolidation of precincts in Los Angeles County during California’s 2003 gubernatorial recall election, and found that turnout at the polling place was reduced by about 3 percentage points among individuals for whom the polling place had changed. Similarly, Cantoni (2020) examined geographic discontinuities in travel distance to polling places based on precinct boundaries, and found that increasing travel distance by about 0.25 miles decreased voter turnout by 2 to 5 percentage points – in our case the relocated precincts moved by an average of about 0.25 miles (although the distance to the polling place did not necessarily increase for all voters in the treated precincts).…”
Section: Discussionmentioning
confidence: 64%
“…The San Francisco Department of Elections selected new polling places for the affected precincts in the days leading up to the election (Sandalow, 1989;San Francisco Department of Elections, 2009). This case represents a credible natural experiment examining how changes in the costs of voting affect political participation, with the "as-if" random assignment of voters to the treatment group determined by earthquake damage to individual buildings rather than election administration decisions which could conceivably be related to turnout, such as precinct consolidation (Brady and McNulty, 2011;McNulty et al, 2009) or the location of precinct boundaries (Cantoni, 2020). We expect that changing the location of a polling place in the days leading up to an election will increase the transportation and search costs of voting, and thus decrease voter turnout (Brady and McNulty, 2011;McNulty et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These and other barriers affect older voters as well. When polling places are moved, voter turnout decreases, especially if the distance to the new polling place increases (Gimpel and Schuknecht 2003;Dyck and Gimpel 2005;Brady and McNulty 2011;Cantoni 2020). These relocations disproportionately affect older voters and voters with disabilities (Brady and McNulty 2011).…”
Section: Voting Rights Achieved and Lost Againmentioning
confidence: 99%
“…A critical factor in citizens' decisions about whether to vote is the distance they need to travel to their polling place. Numerous studies from developed (Brady and McNulty 2011;Cantoni 2019;Haspel and Knotts 2005) and developing democracies (De Kadt 2019; Harris and van der Windt 2019) indicate that citizens' decisions to register to vote and turn out to vote are highly sensitive to the distance they need to travel.…”
Section: Control Of the Electoratementioning
confidence: 99%